Recovery Performance of Primary Agriculture Credit Societies in India: An Assessment - Mazumder, Rabin; Chakravarty, Chandrasekhar; Bhandari, Amit K. (IZA Institute of Labor Economics, 2014)
Agricultural credit is one of the most crucial inputs in all agricultural development programmes. Access of rural credit has still remained scarce in India. Primary Agriculture Credit Societies (PACS) working at grass-root level, having direct contact with the rural people and meet their financial requirements. The problem of loan overdue is a serious concern in different regions of the country, as it affects the recycling of funds and loses its economic viability as a lending institution. The present study examines the recovery performance of rural credit given by PACS in six different regions of India namely Central, Northern, Southern, Eastern, North-East and Western. The result suggests that the performance of credit recovery has been low in north-eastern states and high in northern and southern states. Recovery performance of credit is directly proportional to non-agricultural loan to agricultural loan, trained-untrained staff ratio and average member per society and inversely related with proportion of government capital to working capital and real growth rates at constant price. To make all PACS viable and ensure adequate and timely flow of credit, appropriate policies are required from the Reserve Bank of India in collaboration with State Governments.